THE ROMANIAN LAWYER IN THE EUROPEAN LAW SYSTEM - Marta-Cornelia Ghilea (European Scientific Journal, ESJ, 2013)
With Romania’s accession to the European Union, the practice of the legal profession has known a new dimension. Thus, since 1 January, 2007, Romanian lawyers can practice their profession, occasionally or permanently, in any of the European Union member states, as well as in states that are signatories to the Agreement on the European Economic Area. However, there is an increasing need for uniform and high-level training of lawyers in the European Union, in the context of developing the European integration process. This is mainly due to the very nature of the legal profession, which requires a very high level of competence in relation to the increasing complexity of social and economic relationships, as well as guaranteeing the protection of fundamental citizen rights. The rigorous and in-depth knowledge of national and European law norms, along with ethical correctness in the legal profession, are essential conditions for Bar Associations across Europe in the full implementation of fundamental rights, as recognized in the CCBE Charter regarding the legal profession.